2003
DOI: 10.2135/cropsci2003.1628
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Variation in the Solvent Retention Capacity Test of Wheat Flour

Abstract: type ϫ location effects in soft wheat milling characteristics and cookie quality. Similarly, milling characteristics The solvent retention capacity (SRC) test uses the ability of flour of hard and soft wheat in the presence of artificially to retain a range of solvents as a means of evaluating economically important aspects of wheat (Triticum aestivum L.) quality: pentosan imposed moisture stress were influenced to a greater content, starch damage, gluten strength, and general water retention. degree by genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
73
2
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(92 citation statements)
references
References 8 publications
(16 reference statements)
11
73
2
5
Order By: Relevance
“…The coincident QTL often corresponded to trait correlations (Table 3). The water absorption capacity traits AWRC, WA, SU, and SO were all positively correlated as has been reported by others for soft wheat (Guttieri & Souza, 2003;Ram et al, 2005;Smith et al, 2011;Cabrera et al, 2015;Hoffstetter et al, 2016). There were 10 marker-trait associations from four regions for these traits and only one was not coincident with another.…”
Section: Wheat Quality Laboratory (Swql) Of the United States Departmsupporting
confidence: 81%
See 2 more Smart Citations
“…The coincident QTL often corresponded to trait correlations (Table 3). The water absorption capacity traits AWRC, WA, SU, and SO were all positively correlated as has been reported by others for soft wheat (Guttieri & Souza, 2003;Ram et al, 2005;Smith et al, 2011;Cabrera et al, 2015;Hoffstetter et al, 2016). There were 10 marker-trait associations from four regions for these traits and only one was not coincident with another.…”
Section: Wheat Quality Laboratory (Swql) Of the United States Departmsupporting
confidence: 81%
“…Positive correlations between these two traits have been previously reported (Guttieri et al, 2001;Knott et al, 2009). However, in a study of three soft wheat populations, just one population showed a positive correlation (0.47) between these traits (Guttieri & Souza, 2003). Lack of association of these two traits was also observed in a study of soft white wheat (Guttieri et al, 2001).…”
Section: Wheat Quality Laboratory (Swql) Of the United States Departmmentioning
confidence: 89%
See 1 more Smart Citation
“…Heritability for all traits ranged from 0.67 to 0.90 (Table 4). Others have reported similar heritability values for soft wheat quality traits (Guttieri & Souza, 2003;Smith et al, 2011;Cabrera et al, 2015;Hoffstetter et al, 2016).…”
Section: Wheat Quality Laboratory (Swql) Of the United States Departmmentioning
confidence: 64%
“…Previous correlation studies of soft wheat quality traits have already shown that flour damaged starch and arabinoxylan levels may be controlled by common genetic factors (Guttieri about the heritability of SRCs in soft wheat have shown high heritability (Guttieri & Souza, 2003;Smith et al, 2011;Cabrera et al, 2015;Hoffstetter et al, 2016). Common QTLs for AWRC and damaged starch were observed in a hard x soft population on chromosome 4DL (Campbell et al, 2001).…”
Section: Introductionmentioning
confidence: 96%